2012
DOI: 10.1002/ejic.201200469
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Thermal Decomposition of Lanthanide(III) and Actinide(III) Oxalates – from Neodymium and Cerium to Plutonium

Abstract: Lanthanides are often used as surrogates to study the properties of actinide compounds. Their behaviour is considered to be quite similar as they both possess f valence electrons and are close in size and chemical properties. This study examines the potential of using two lanthanides (neodymium and cerium) as surrogates for plutonium during the thermal decomposition of isomorphic oxalate compounds, in the trivalent oxidation state, into oxides. Thus, the thermal decomposition of neodymium, cerium and plutonium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Nevertheless, the heat treatments combining the use of oxidizing and reducing atmospheres appeared to be much more efficient to operate the carbon elimination. Again, this observation could be correlated with the Boudouard equilibrium that led to the disproportionation of CO into C and CO 2 under inert atmosphere [36]. In these conditions, the amount of carbon still remaining in the samples heated in reducing atmosphere was systematically found to be 4 to 5 times higher than that measured in samples previously calcined in air.…”
Section: Variation Of Carbon Contentmentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, the heat treatments combining the use of oxidizing and reducing atmospheres appeared to be much more efficient to operate the carbon elimination. Again, this observation could be correlated with the Boudouard equilibrium that led to the disproportionation of CO into C and CO 2 under inert atmosphere [36]. In these conditions, the amount of carbon still remaining in the samples heated in reducing atmosphere was systematically found to be 4 to 5 times higher than that measured in samples previously calcined in air.…”
Section: Variation Of Carbon Contentmentioning
confidence: 82%
“…Nevertheless, if the dehydration step still occurred in the same range of temperature, the decomposition of oxalate species was found to take place at lower temperature as it ended below 350 • C. Such difference could be ascribed to the more efficient elimination of the carbon species in air. Indeed, in such conditions, CO coming from the decomposition of C 2 O 4 species is mainly oxidized by O 2 while it tends to disproportionate under inert or reducing atmosphere to form CO 2 and elemental carbon (Boudouard equilibrium) [36]. Moreover, an additional weight loss was pointed out at around 650 • C and could be ascribed to the transformation of an intermediate uranium carbonate or oxocarbonate into the final oxide product, probably as U 3 O 8 .…”
Section: Thermogravimetric Analysesmentioning
confidence: 97%
“…For the Pu-containing compositions, the formation of the Pu III -oxalate intermediate might be possible. 20,21 Finally, the resulting NCs were washed with water, ethanol, and acetone, in order to gradually decrease the polarity of the solution. In the case of the uranium-containing samples, the work was performed under argon and using minute amounts of hydrazine, in order to limit the oxidation of U IV .…”
Section: Sample Preparationmentioning
confidence: 99%
“…The low temperature calcined oxide powders generally kept their original morphology of the precipitated oxalates [11]. Cerium oxalate with the layered structure, which mostly kept its morphology by calcination up to 1000°C, was also showed previously [12]. Therefore, it can be suggested that the mixed rare earth oxalate could show layered structure, though; we haven't observed it by an analytical technique.…”
Section: Resultsmentioning
confidence: 66%